Madagascar - Savings and Loans - World Bank (Washington, DC, 2012)
The first savings and loan associations (SLAs - mutuelles d'epargne et de credit) were established in Madagascar in 1993 under a pilot project supported by the World Bank. By the time the project closed in December 1997, 54 SLAs had been established in four regions, Toamasina, Lac Alaotra, Fianarantsoa and Haute-Mania, and they had started to group themselves into regional unions. The lessons learned from this pilot project are being factored into the preparation of the follow-up project. The main lesson is that it takes more effort to maintain and develop Microfinance Institutions (MFIs) than to create them. The enthusiasm of donors to provide assistance in microfinance and the lack of readiness of the government to receive it resulted in duplications and contradictions. These can be avoided in the future by a well-defined national strategy on microfinance. To progress towards self-sustainability, MFIs must also move into urban areas where population density helps to lower the costs of delivering financial services and where savings can be more readily mobilized to support growth.